INTERNATIONAL EXPERIENCE IN DIGITALIZATION OF AGRICULTURE AND POSSIBILITIES OF ITS APPLICATION IN ARMENIA - Ashot Voskanyan; Anna Kartashyan; Haik Garabedian (Journal of Bio-Based Marketing)
The article reflects the peculiarities of the digitalization of agriculture in different countries, including the Republic of Armenia. The article considers revealing the international experience in digitalization of agriculture and identification of the ways that would be applicable also in Armenia. Studies and analyses of the digitalization in agriculture in several developed and developing countries, including the state support policies aimed at digitalization and the feasibility of the application thereof in Armenia were carried out, with digitalization measures suggested. The timeliness of the study is that today, it is impossible to increase the competitiveness of agriculture without digital solutions. Meanwhile, within the framework of the RA Government’s 2021-2026 Programme for Activity Measures, support for the development of digital agriculture has been defined as one of the measures to develop overall agriculture and to increase its productivity. The results of the studies and analyses can serve as a basis for developing and implementing measures aimed at the digitalization of agriculture in the Republic